Human Migration in the Arctic The Past, Present, and Future - Uusiautti, Satu; Yeasmin, Nafisa (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2019)
This book discusses the past, present, and future of migration in the Arctic. It addresses many of the critical dynamics of immigration and migration, and emerging challenges that now confront the region. What can be learned from the past? What are the challenges and solutions of tomorrow? Migration in the Arctic is a fascinating and topical - but less studied - phenomenon that influences various societal levels, such as education. The book introduces research on economic, social, and educational perspectives of migration in the region. It provides analysis of minorities immigrating to the North without neglecting the viewpoint of indigenous people of the Arctic. Contributors comprise researchers from various Arctic countries. Multidisciplinary research provides a unique viewpoint to the theme. The book is suitable for researchers and teachers of higher education as well as anyone interested in Arctic studies and (im)migration.